The analysis of influencing factors on the going concern audit opinion – a study in manufacturing firms in Indonesia - Thomas Averio (Asian Journal of Accounting Research, 2020)
It is argued that the going concern opinion is issued if auditors have a doubt about financial condition of a company. Provision of the going concern audit opinion may worsen the company in terms of gaining public trust and may even indicate bankruptcy. This study aims to determine the factors that affect the auditor's going concern opinion.This research used secondary data obtained from annual reports and independent audit reports published by the Indonesia Stock Exchange. The population of this research included manufacturing firms registered in the Indonesia Stock Exchange from 2015 to 2019. The sample after the purposive sampling technique being applied consisted of 33 companies. The data were analyzed using logistic regression performed in the statistical analysis software, SPSS 24.0.The results indicated that leverage positively affected the going concern audit opinion, then the audit quality, profitability and liquidity negatively affected the going concern audit opinion, whereas firm size and audit lag did not affect the going concern audit opinion.This study is in contrast to several existing studies on the determinants of the auditor's going concern opinion and provides knowledge on developing more factors affecting the auditor's going concern opinion.